Evaluation of some management practices for the suppression of cucurbit fruit fly in bitter gourd (Journal of the Bangladesh Agricultural University, 2010)
The experiment was conducted at Sher-e-Bangla Agricultural University farm, Dhaka, Bangladesh during the period from March to June 2007 with seven treatments viz; T1: Hand picking of infested fruits of bitter gourd at 7 days interval; T2: Neem seed kernel at 5 gm/l of water at 5 days interval +T1; T3: Spray of shobicron 425EC @ 2ml/l of water at 7 days interval + T1; T4: Micronutrient-Zn @ 6.72kg/ha; T5: Micronutrient-B @ 1.96kg/ha; T6: Micronutrient Zn + B and T7: Untreated control. The lowest fruit infestation (13.78%) by weight was recorded from the treatment T2, while the highest (46.09%) fruit infestation by weight was recorded from T7 untreated control. The highest (85.00) number of fruits per plot was recorded for T2 treated plots while the lowest (61.00) number of fruits per plot was recorded from the untreated control T7. The application of neem seed kernel at 5 days interval + hand picking of infested fruits in T2 treated plots gave the highest yield (12.88 t/ha) while it was lowest (10.02 t/ha) in T7 untreated control plots. The combined application of micronutrients was more effective in T6 than the single application of micronutrients in T4 and T5 respectively. The results of economic analysis of bitter gourd showed that the highest benefit cost ratio (9.44) was estimated for T6 treatment and the lowest (1.06) benefit cost ration for T3 treatment. Among the different treatments neem seed kernel at 5 days interval + hand picking of infested fruits in T2 treated plots was more effective than the insecticide Shobicron 425 EC at 7 days interval + hand picking of infested fruits followed by the T6 treated plots in combination of micronutrients Zn +B. Keywords: Cucurbit fruit fly; Bitter gourd; Various management practices DOI: 10.3329/jbau.v8i1.6393J. Bangladesh Agril. Univ. 8(1): 23-28, 2010